141k views
3 votes
List the first 9 terms of the sequence defined recursively by Sn = Sn-2. (Sn-1 - 1), with S1 = 2 and

S2 = 3

User HackerGil
by
4.6k points

1 Answer

1 vote

Step-by-step explanation

Given that Sn = Sn-2 . (Sn-1 - 1)

Tn = Sn - Sn-1

Tn = Sn-2 . (Sn-1 - 1) - (Sn-3 . (Sn-2 - 1))

T3 = S1.(S2-1) - (S0.(S1-1)

T3 = 2.(3-1) - 1.(2-1)

T3 = 2(2) - 1(1)

T3 = 4-2

T3 = 3

T4 = S2.(S3-1) - (S1.(S2-1)

T4 =3.(-1) - 1.(2-1)

T4 = 2(2) - 1(1)

T4 = 4-2

T4 = 3

User Adanlif
by
4.4k points